Knowledge, attitude and practive of cardiopulmonary resuscitation among nigerian physiotherapists - Mbada, Chidozie Emmanuel; Hakeem, Bada Olalekan; Adedoyin, Rufus Adesoji; Awotidebe, Taofeek Oluwole; Okonji, Adaobi Margaret (Journal of Respiratory and CardioVascular Physical Therapy, 2015)
Objective: There is an apparent dearth of studies on physiotherapists’ knowledge and competence in Cardiopulmonary Resuscitation (CPR). This study assessed knowledge, attitude and practice of CPR among Nigerian physiotherapists. Methods: This cross-sectional study involved 140 physiotherapists from seven selected hospitals in South-western Nigeria, yielding a response rate of 87.5%. A self-administered questionnaire which sought information on knowledge, attitude, and practice of CPR was used as the survey instrument. Data were also obtained on socio-demographic and occupational characteristics. Data was analyzed using descriptive and inferential statistics at 0.05 Alpha level. Results: More than half (63.6%) of the respondents had within poor to average knowledge of CPR. 55% of the respondents demonstrated positive attitude towards CPR while only 17.1% respondents had ever performed CPR. 92.1% respondents answered correctly questions seeking to know “when CPR is most effective” and 25% knows the correct compression to ventilation ratio. Only, 20.7% knew the steps of CPR in the correct sequence and 18.6% knew the correct chest compression landmark. Mandatory training in CPR was recommended as graduation requirement for physiotherapy (92.1%). Conclusion: Nigerian physiotherapists had poor to average knowledge but positive attitude towards CPR practice. Nigerian physiotherapists had a low CPR practice frequency attributable to lack of opportunity to practice CPR or lack of adequate knowledge.